Aktualisasi NDP dalam Mewujudkan Pelayanan Kesehatan yang Berkeadilan: Sebuah Literature Review - Annisa Lutfia Frida Shafira (STAI DDI Kota Makassar, 2020)
Indonesia is a country that aspires to social justice, strives to form a state structure that can improve the welfare of society in accordance with the mandate of the 1945 Constitution. Healthcare and Social Security Agency (BPJS) is the organizer of social security to realize welfare in the health sector. The concept of the National Health Insurance (JKN) is here to ensure that all Indonesian citizens get comprehensive, fair and equitable health services. The purpose of this study was to see the effect of patient participation status on the quality of health services as seen from the level of patient satisfaction. The existing patient participation status is BPJS patients and non-BPJS patients. This research was conducted using the literature study method with a collection of a number of scientific journals that are relevant to the problem being studied. The collected data were analyzed by means of qualitative descriptive analysis using three variables, namely patient participation status, patient satisfaction level and quality of health services. The results showed that there were differences in the quality of health services for BPJS and non-BPJS patients seen from the level of patient satisfaction.